The Dynamics of Public Policy for Non-Permanent Teachers in Semarang, Indonesia - Ngabiyanto, Ngabiyanto; Kameo, Daniel Daud; Wiloso, Pamerdi Giri; Ismanto, Bambang (Political Science Program, Universitas Negeri Semarang, 2019)
This study examines the problems of non-permanent teachers from two sides. First, non-permanent teachers from the perspective of public policy. The focus of this study is on the government's reaction to the demands of non-permanent teachers formulated in legislation. Second, the government's strategy to accommodate the aspirations of non-permanent teachers and efforts to resolve the problems of non-permanent teachers through various public policies that are risen. This study is a follow-up to the implementation of research on non-permanent teachers in Semarang city. The data is taken based on the rules of qualitative research with in-depth interviewing techniques to obtain data in the field, especially primary data types. The results of this study find several interesting things. First, there is a change in orientation of non-permanent teachers from service to a struggle in improving social status and welfare. Second, the income of being a non-permanent teacher is not feasible to meet the minimum living needs of non-permanent teachers and their families. Third, public policy as the government's reaction to the demands of non-permanent teachers can be categorized into 5 models, they are: (1) Political Lobbying Model; (2) Blessing Amendment Model; (3) Impartial policy model; (4) Partial Policy Model; and (5) Response Policy Model. From these findings, it can be seen that the uniqueness of this study is the finding of the models of public policy which are a form of government reaction to the demands of non-permanent teachers.